A The Effectiveness of Leaflets and Video Media in Increasing Knowledge About Breast Self-Examination (SADARI) - Anggia Sari; Yunita Lestari; Has’ad Rahman Attamimi; Rai’in Rai’in (Jurnal Penelitian Pendidikan IPA, 2022)
Breast cancer is a health problem and a cause of death for women worldwide. Breast cancer worldwide more than 508,000 women died in 2011 due to breast cancer. Cancer or malignant tumors are uncontrolled growth of cells/tissues, keep growing/increasing, immortal (cannot die). The breast is the number one site for cancer growth in women). If breast cancer is found at an early stage, the cure rate for sufferers is still higher than at an advanced stage. The purpose of this study was to determine the effectiveness of leaflet and video media in increasing knowledge about breast self-examination (SADARI) in midwifery diploma students in semester 1. This study used a comparative quantitative design. The sample in this study were all D3 midwifery study program students in semester 1, the sample in this research was 32 students who were taken by total sampling, the data analysis used was Kruskal Wallis. It can be concluded based on the results of further tests on the effect of applying leaflet and video media to midwifery students' knowledge in semester 1 about SADARI between before and after being given treatment, each group has significant differences, both when tested together or separately